E-277 The optimal timing for resumption of anticoagulation/antiplatelet after an intracerebral hemorrhage: the everlasting question. (23rd July 2022) - El Naamani, K; Abbas, R; Sweid, A; Tjoumakaris, S; Gooch, M; Herial, N; Hasan, D; Rosenwasser, R; Jabbour, P
Abstract : Background: The number of patients presenting for intracerebral hemorrhage and taking anticoagulation/antiplatelets for other comorbidities is increasing. Till now, no consensus has been reached in finding the optimal timing of anticoagulation/antiplatelet ( AC/AP) resumption that protects against thromboembolic events and prevents hemorrhage recurrence. Objective: To assess the best time for resumption AC/AP in patients presenting with intracerebral hemorrhage (ICH). Methods: This is a retrospective observational study including patients presenting with ICH while on AC/AP. Patients were identified by searching the prospectively maintained database of patients with ICH between 2015 and 2020. Patients were followed up for a full year to assess the effect of resumption and discontinuation of AC/AP on hemorrhagic and thrombotic complications. Result: In our study, the mean duration for AC/AP resumption was 19 days. During this time, 6 (8.1%) patients suffered from thrombotic events which was comparable to the literature. Moreover, none of the patients in our study developed any hemorrhagic events after AC/AP resumption. Conclusion: As a conclusion, our study showed that discontinuing AC/AP, especially AC or a combination of AC and AP, caused thrombotic events compared to AC/AP resumption which had no significant hemorrhagic complications regardless of the timing of resumption. Disclosures: K. El Naamani: None. R. Abbas: None. A. Sweid: None. S. Tjoumakaris: 2; C; Medtronic, Microvention. M. Gooch: 2; C; Stryker. N. Herial: None. D. Hasan: None. R. Rosenwasser: None. P. Jabbour: 2; C; Medtronic, Microvention, Balt, Cerus Endovascular.